Development and Evaluation of An Abbreviated Extracorporeal Membrane Oxygenation (ECMO) Course for Nonsurgical Physicians and Nurses. Issue 4 (16th April 2020) - Maddry, Joseph K.; Paredes, R. Madelaine; Paciocco, Joni A.; Castaneda, Maria; Araña, Allyson A.; Perez, Crystal A; Reeves, Lauren K.; Newberry, Ryan K.; Bebarta, Vikhyat S.; Kester, Nurani; Mason, Phillip E.
Abstract: Background: Extracorporeal membrane oxygenation (ECMO) is a modification of cardiopulmonary bypass that allows prolonged support of patients with severe respiratory or cardiac failure. ECMO indications arse rapidly evolving and there is growing interest in its use for cardiac arrest and cardiogenic shock. However, ECMO training programs are limited. Training of emergency medicine and critical care clinicians could expand the use of this lifesaving intervention. Our objective was to develop and evaluate an abbreviated ECMO course that can be taught to emergency and critical care physicians and nurses. Methods: We developed a training model using Yorkshire swine ( Sus scrofa ), a procedure instruction checklist, a confidence assessment, and a knowledge assessment. Participants were assigned to teams of one emergency medicine or critical care physician and one nurse and completed an abbreviated 8‐hour ECMO course. An ECMO specialist trained participants on preparation of the ECMO circuit and oversaw vascular access and ECMO initiation. We used the instruction checklist to evaluate performance. Participants completed confidence and knowledge assessments before and after the course. Results: Seventeen teams (34 clinicians) completed the abbreviated ECMO course. None had previously completed an ECMO certification course. Immediately following the course, all teams successfully primed and prepared the ECMO circuit. Fifteen teams (88%, 95% confidence interval [CI] = 64% to 99%) successfully initiated ECMO. Participants improved their knowledge (difference 21.2, 95% CI = 16.5 to 25.8) and confidence (difference 40.3, 95% CI = 35.6 to 45.0) scores after completing the course. Conclusions: We developed an accelerated 1‐day ECMO course. Clinicians' confidence and knowledge assessments improved and 88% of teams could successfully initiate venoarterial ECMO after the course.